Development of a force sensing system to measure the ground reaction force of rats with spinal cord injury (SCI) undergoing gait rehabilitation training - Sei, Eng Kiat (2018)
Spinal cord injury is a worldwide health issue with severe monetary, health, and psychological implications. There are numerous on-going researches on the treatment methods of spinal cord injury. Rodents are commonly used in these researches due to their similarity to humans. Different approaches have been developed to assess the recovery progress. This project seeks to explore the possibility of using ankle flexion as a mean of assessment for assessing rodents with complete spinal cord injuries. The test subjects were restraint, and an upward force was applied on their paw to flex it upwards. Force sensors are placed beneath the paw. It is hypothesised that better recovered test subjects would resist the motion to a greater extent. A total of 6 rats were tested using the set up. All rats received the same medical treatment but only 3 of the rats had underwent 6 weeks of rehabilitation training. Results obtained showed significant differences between rehabilitation rats and non-rehabilitation rats. This proves the viability of using ankle flexion as a means of assessment for spinal cord injury treatments.